Senam Hipertensi Pada Lansia Di Rt 33 RW 04 Kelurahan Pematang Gubernur - Simanjuntak, Florance Lestari; Arin Melinda; Cindy Afrianis; Merry Dayati; Najah Febina; Jumita; Rohani, Tuti; Danur Azissah (Jurnal Pengabdian Mitra Persada, 2025)
Hypertension is a health problem that is often faced by everyone as a result of a decrease in body function as people age. This study aims to measure the extent to which hypertension exercise can help reduce blood pressure and improve quality of life. Demonstrative research method, and the population in this research are people who live on Rt 33 Rw 04, Pematang Governor Village, Bengkulu City. The research sample was 35 people. The research instruments were hypertension exercises and blood pressure measurements, observation sheets, and blood pressure meters. Research results: Of the total population, 17 people had hypertension. The research results showed that the average blood pressure for 35 respondents was 131/83 mmHg. Based on the analysis of research results, it was concluded that hypertension exercise was effective as a non-pharmacological therapy for lowering blood pressure.